Are pure or hybrid strategies right for new ventures in transition economies?. (December 2015) - Manev, Ivan M; Manolova, Tatiana S; Harkins, Jason A; Gyoshev, Bojidar S
This article examines the role of strategic intensity or commitment to a chosen course of action, and the impact of pure versus hybrid competitive strategies on competitive performance in transition economies, using survey data ( N  = 333) from Bulgaria. We find that strategic intensity is positively related to performance; firms that deviate from pure cost leadership or differentiation and achieve a balance on both dimensions report superior performance. In a post hoc analysis of our data, we find preliminary evidence that strategic intensity may act as a mediator of the relationship between strategic type and performance.